2021
DOI: 10.1186/s11689-021-09397-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SHANK3 deficiency in animal models: phenotypes, treatment strategies, and translational implications

Abstract: Background Autism spectrum disorder (ASD) is a neurodevelopmental condition, which is characterized by clinical heterogeneity and high heritability. Core symptoms of ASD include deficits in social communication and interaction, as well as restricted, repetitive patterns of behavior, interests, or activities. Many genes have been identified that are associated with an increased risk for ASD. Proteins encoded by these ASD risk genes are often involved in processes related to fetal brain developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 259 publications
0
64
0
Order By: Relevance
“…In addition to this, the generation and analysis of mice lines lacking different SHANK3 isoforms have revealed insights into SHANK3 relevance at the synapses. At the morphological level, these animals showed reduced dendritic spine density with longer spines and no alterations in the PSD ultrastructure [ 9 ], while others exhibited reduced dendritic spine density and smaller PSD [ 10 , 11 ]. Furthermore, the PSDs of these animals are known to have fewer proteins responsible for local actin remodeling as well as other synaptic proteins, such as Homer [ 10 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, the generation and analysis of mice lines lacking different SHANK3 isoforms have revealed insights into SHANK3 relevance at the synapses. At the morphological level, these animals showed reduced dendritic spine density with longer spines and no alterations in the PSD ultrastructure [ 9 ], while others exhibited reduced dendritic spine density and smaller PSD [ 10 , 11 ]. Furthermore, the PSDs of these animals are known to have fewer proteins responsible for local actin remodeling as well as other synaptic proteins, such as Homer [ 10 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SHANK3 gene encodes a scaffold protein (SHANK3) enriched in the post-synaptic density of excitatory synapses and is currently one of the best characterized risk genes in ASD ( Monteiro and Feng, 2017 ). Several studies have shown that Shank3 mutations in zebrafish ( Liu et al, 2018 ), mice ( Mei et al, 2016 ; Zhou et al, 2016 ), rats ( Song et al, 2019 ), and even primates ( Zhou Y. et al, 2019 ), lead to reduced social interaction and repetitive behaviors, as well as other numerous defects ( Peça et al, 2011 ; Zhou et al, 2016 ; Delling and Boeckers, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Knock-down experiments in primary neurons ( Verpelli et al, 2011 ) and human-induced pluripotent stem cell–derived cells including enterocytes ( Pfaender et al, 2017 ), neurons ( Shcheglovitov et al, 2013 ; Lutz et al, 2020 ), and muscle cells ( Lutz et al, 2020 ) have been performed and various mouse models have been generated carrying different deletions and mutations of SHANK3 ( Jiang and Ehlers, 2013 ; Delling and Boeckers, 2021 ). Interestingly, these SHANK3-deficient mouse models manifest with different phenotypes dependent on the location of the deletion in Shank3 ( Delling and Boeckers, 2021 ). Dependent on multiple internal promotors, six different isoforms of SHANK3 are known, and with alternative splicing at least 10 SHANK3 isoforms can be generated ( Wang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%